ҚУШ ПАТИ МЕТАФОРАСИ (Қорақалпоқ халқ эртаклари мисолида) - Кунназарова, Ш.М. (SCIENCE and SOCIETY, 2025)
The article analyzes examples of the bird feather metaphor in folk tales. It examines the feather metaphor in relation to the national values and traditions of the Karakalpak people, and discusses its roots